1994
DOI: 10.7883/yoken1952.47.141
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of Aspergillus and Penicillium Species From Respiratory Specimens by Polymerase Chain Reaction (Pcr)

Abstract: SUMMARY: A polymerase chain reaction (PCR) method capable of detecting both Aspergillus fumigatus infections, pulmonary non-fumigatus Aspergillus species (spp.) and Penicillium spp. from clinical specimens was established.The primer pair was designed on the basis of the sequence of the 18S-ribosomal RNA gene of A. fumigatus and P. notatum. A 385 by product was successfully amplified by this PCR method from all of 12 medically important Aspergillus spp. and Penicillium spp. (38 strains), but not from human, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Previous studies evaluating PCR-mediated detection of Aspergillus species showed significantly high rates of sensitivity but involved assays with different methods and objectives, partly for optimization of culture assays (37) and partly for typing in epidemiological studies (3,4).…”
mentioning
confidence: 99%
“…Previous studies evaluating PCR-mediated detection of Aspergillus species showed significantly high rates of sensitivity but involved assays with different methods and objectives, partly for optimization of culture assays (37) and partly for typing in epidemiological studies (3,4).…”
mentioning
confidence: 99%
“…but also Penicillium spp. (5). However, this does not hamper the interpretation of our results, because Penicillium spp.…”
Section: Discussionmentioning
confidence: 71%
“…PCRlabeling probe for identification A 385 bp sequence of 1 8S ribosomal RNAfrom A.fumigatus was selected for probe synthesis (5,6). Multiple digoxigenin molecules-bearing probes were produced by PCRaccording to a method reported previously with modification (7).…”
Section: Methodsmentioning
confidence: 99%
“…As realized successfully for other pathogenic organisms difficult to detect (for example cytomegalovirus [39], Borrelia burgdorferi [40] and Toxoplasma gondii [41]), more sensitive and rapid detection assays have been established by the use of the polymerase chain reaction method (PCR). PCR-based detection methods for fungi have been developed successfully since multicopy gene targets were identified and sequenced [42][43][44][45][46]. Previous studies for the evaluation of PCR-mediated detection of fungi showed significantly improved sensitivity, but were performed with methodically different assays and different objectives, partly to optimize culture assays [47], partly for typing in epidemiological studies [48,49], mainly in nonclinical settings [50].…”
Section: Noncultural Methods To Detect Candida Speciesmentioning
confidence: 99%
“…5 of 7 BAL samples of patients, who had radiological evidence of invasive pulmonary aspergillosis, showed positive PCR signals; in their investigation the galactomannan ELISA showed less false-positive results with BAL samples. With another assay, Makimura et al [42,43] obtained PCR products from BAL of immunocompromised and neutropenic patients, but no amplicons were obtained from immunocompetent individuals. Bretagne et al [73] pointed to the high risk of BAL specimen contamination by Aspergillus conidia resulting in approximately 23% of false-positive results.…”
Section: Noncultural Methods To Detect Aspergillus Speciesmentioning
confidence: 99%